Perbedaan Pola Asuh Demokratis dengan Pola Asuh Otoriter terhadap Kedisiplinan Siswa di Kelas VI SD Nurul Hasanah - Dina Hidayati Hutasuhut; Widya Utami Lubis (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
This study aims to: determine the discipline of students with democratic parenting in SD Nurul Hasanah, determine the discipline of students with authoritarian parenting and determine the difference between democratic parenting and authoritarian parenting on student discipline in grade VI SD Nurul Hasanah. This type of research is a comparative study using a quantitative approach. The sample of this study were all students of class VI SD Nurul Hasanah as many as 28 people. The data collection technique used in this research is a questionnaire. Where before the questionnaire was distributed to the sample, the questionnaire was tested for validation first. The results of this study are: based on student discipline questionnaires that have been distributed to students with a tendency to democratic parenting, the highest score obtained by students is 80 and the lowest score is 60. With t count (6.50666 > 1.70), it can be concluded that there are differences between democratic parenting and authoritarian parenting on student discipline in grade VI SD Nurul Hasanah